Hybrid magnetite–gold nanoparticles as bifunctional magnetic–plasmonic systems: three representative cases. Issue 4 (24th April 2017) - Canet-Ferrer, J.; Albella, P.; Ribera, A.; Usagre, J. V.; Maier, S. A.
Abstract : Controlling the electromagnetic field distribution of magnetite–gold hetero-structures by tailoring the geometry of the magnetic- and plasmonic-constituents. Abstract : Hybrid systems based on magnetite and gold nanoparticles have been extensively used as bifunctional materials for bio- and nano-technology. The properties of these composites are assumed to be closely related to the magnetite to gold mass ratio and to the geometry of the resulting hetero-structures. To illustrate this, we compare and analyze the optical and magnetic properties of core–shell, dumbbell-like dimers and chemical cross-linked pairs of magnetite and gold nanoparticles in detail. We explore how the combination of gold with magnetite can lead to an improvement of the optical properties of these systems, such as tunability, light scattering enhancement or an increase of the local electric field at the interface between magnetic and plasmonic constituents. We also show that although the presence of gold might affect the magnetic response of these hybrid systems, they still show good performance for magnetic applications; indeed the resulting magnetic properties are more dependent on the NP size dispersion. Finally, we identify technological constraints and discuss prospective routes for the development of further magnetic–plasmonic materials.